Th1 Cytokine-Secreting Recombinant Mycobacterium bovis Bacillus Calmette-Guérin and Prospective Use in Immunotherapy of Bladder Cancer - Yi Luo; Jonathan Henning; Michael A. O'Donnell (Clinical and Developmental Immunology)
Intravesical instillation of Mycobacterium bovis bacillus Calmette-Guérin (BCG) has been used for treating bladder cancer for 3 decades. However, BCG therapy is ineffective in approximately 30–40% of cases. Since evidence supports the T helper type 1 (Th1) response to be essential in BCG-induced tumor destruction, studies have focused on enhancing BCG induction of Th1 immune responses. Although BCG in combination with Th1 cytokines (e.g., interferon-α) has demonstrated improved efficacy, combination therapy requires multiple applications and a large quantity of cytokines. On the other hand, genetic manipulation of BCG to secrete Th1 cytokines continues to be pursued with considerable interest. To date, a number of recombinant BCG (rBCG) strains capable of secreting functional Th1 cytokines have been developed and demonstrated to be superior to BCG. This paper discusses current rBCG research, concerns, and future directions with an intention to inspire the development of this very promising immunotherapeutic modality for bladder cancer.